2021
DOI: 10.1016/j.eiar.2021.106596
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on, and revising, international best practice principles for EIA follow-up

Abstract: Follow-up is a vital component of Environmental Impact Assessment (EIA), being essential for understanding assessment outcomes. Long-standing international best practice principles for EIA follow-up are reviewed, and revisions proposed, based on workshops with academics and practitioners, literature review and self-reflection. The proposed revision of EIA follow-up principles will feature an introduction with a simple definition and explanation of objectives for follow-up, and 15 principles. The revised princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…74 good practices for EIA are proposed [11] , grouped under 22 themes. International best practice principles for EIA follow-up, a vital element of EIA, are reviewed, and the revised EIA follow-up best practice principles are proposed [59] .…”
Section: Eia Good Practicesmentioning
confidence: 99%
See 3 more Smart Citations
“…74 good practices for EIA are proposed [11] , grouped under 22 themes. International best practice principles for EIA follow-up, a vital element of EIA, are reviewed, and the revised EIA follow-up best practice principles are proposed [59] .…”
Section: Eia Good Practicesmentioning
confidence: 99%
“…Citing references rather than describing theory in the EIA report can reduce its bulk. Good practice EIA entails that the EIA report is written in such a manner that different chapters are linked with each other and properly documented [31] to facilitate EIA review, derive terms and conditions for EC [69] , and aid EIA follow-up [59,70,71] .…”
Section: Eia Report Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…As Pinto et al (2019) and Morrison-Saunders et al (2021) identified, EIA follow-up and impact management can facilitate public accountability of decisionmaking in all levels of government when implemented effectively (see also Arts 1998). However, there is limited capacity for project-scale assessment reports to influence post-approval changes in either project design or the political, economic, environmental or social context in which projects develop.…”
Section: Strategic Urban Planning and Managing Social Issuesmentioning
confidence: 99%